G534(P) Prevention of late onset sepsis and central line associated blood stream infection in preterm infants. (7th April 2014) - Murthy, V; Nath, P; Millar, M; Morris, J; Sinha, AK
Abstract : Late onset sepsis (LOS) and Central line associated blood stream infection (CLA-BSI) remains a major cause of mortality and morbidity in preterm infants. Numerous interventions were introduced between 2007 and 2012, aiming to reduce hospital based infections. Aim: To investigate the effects of hospital wide and local interventions on LOS and CLA-BSI rates in preterm infants born at <32 weeks gestation. Methods: Bed care days (BAPM 2001 standards)and catheter days were obtained from Neonatal database, positive blood cultures were obtained from Microbiology laboratory database. Results: Significant reduction in rates of LOS and CLA-BSI from 2007 to 2012 (Table 1 ) was observed. Poisson regression methods showed reduction in rates to be related to change in policy of antimicrobial use (p < 0.001), introduction of 2% chlorhexidine for catheter care (p < 0.05), aseptic non touch technique (ANTT) for CLA-BSI (p < 0.01); Trust wide audits and ANTT for LOS rates (p < 0.001). Conclusions: A multifaceted approach involving a change in local health care policy, education, training and surveillance can reduce catheter related infections and late onset sepsis in the Neonatal unit.